EFFECTS OF PHOSPHATE IONS ON INTERGRANULAR PRESSURE SOLUTION IN CALCITE: AN EXPERIMENTAL STUDY - Zhang X.; Spiers C.J. (My University, 2005)
Intergranular pressure solution (IPS) is a coupled chemical-mechanical process of widespread importance that occurs during diagenesis and low-temperature deformation of sedimentary rocks. Laboratory experiments on IPS in halite, quartz, and calcite have largely concentrated on the mechanical aspects of the process. In this study, we report the effects of pore fluid chemistry, specifically varying phosphate ion concentration, on the mechanical compaction by IPS of fine-grained calcite powders at room temperature and 1 to 4 MPa applied effective stress. Phosphate was investigated because of its importance as a biogenic constituent of sea and pore waters. Increasing the pore fluid phosphate concentration from 0 to 10−3 mol/L systematically reduced compaction strain rates by up to two orders of magnitude. The sensitivity of the compaction strain rate to phosphate concentration was the same as the sensitivity of calcite precipitation rates to the addition of phosphate ions reported in the literature, suggesting that the rate of IPS in phosphate-bearing samples was controlled by calcite precipitation on pore walls. The results imply that IPS and associated porosity/permeability reduction rates in calcite sediments may be strongly reduced when pore fluids are enriched in phosphates, for example, through high biologic productivity or a seawater origin. Future modeling of IPS-related processes in carbonates must therefore take into account the effects of pore fluid chemistry, specifically the inhibition of interfacial reactions.